Lexical loans in the field of modern technologies from Spanish to Quechua Chanca from the Puncuhuacca annex - Ccaccachahua Huamaní, Bertha (2022)
In this article the lexical loanwords from Spanish in the Chanca Quechua of the Puncuhuacca annex are described. The methodology used is qualitative. The data has been collected from interviews with bilingual speakers of different levels of education, which are organized into four semantic fields: the field of modern technology, technology in school supplies, technology in clothing and technology. in kitchen utensils. The focus and level of study is qualitative-descriptive. The results show that the lexical loans of the technologies have been incorporated into the speech of the Quechua speakers of Puncuhuacca due to communicative needs, thus adapting to the phonological and morphological system of Quechua.